Role of tau phosphorylation in formation of tau envelopes - Karhanová, Adéla (Univerzita Karlova, Přírodovědecká fakulta, 2023)
Tau is an intrinsically-disordered microtubule-associated protein important for axonal development and a critical regulator of microtubule functions in axons. Tau activity is controlled by phosphorylation and its deregulation resulting in tau hyperphosphorylation and aggregation has been linked to multiple neurodegenerative disorders, collectively termed tauopathies. On microtubules, tau molecules segregate into two kinetically distinct phases, consisting of either independently diffusing molecules or interacting molecules that form cohesive "envelopes" around microtubules. Tau envelopes regulate the action of other microtubule-associated proteins, such as the motility of molecular motors, and protect microtubules against degradation by microtubule-severing enzymes. How the formation, dynamics, and function of tau envelopes are regulated, however, is unknown. Here we show that tau phosphorylation impedes the formation and functioning of protective tau envelopes. Using a combination of reconstitution experiments and live cell imaging, we show that phosphorylated tau incorporates into tau envelopes and that it slows down the envelope growth. Importantly, we demonstrate that phosphorylated tau also destabilizes already existing envelopes leading to their disassembly. Together, our results demonstrate. Tau je nestrukturovaný protein asociovaný s mikrotubuly důležitý pro vývoj axonů a kritický regulátor funkcí mikrotubulů v axonech. Aktivita Tau je řízena fosforylací a její deregulace vedoucí k hyperfosforylaci a agregaci tau je spojena s četnými neurodegenerativními poruchami, souhrnně nazývanými tauopatie. Na mikrotubulech se molekuly tau segregují do dvou kineticky odlišných fází, které se skládají buď z nezávisle difundujících molekul, nebo interagujících molekul, které tvoří soudržné "obálky" kolem mikrotubulů. Tau obálky regulují působení jiných proteinů asociaovaných s mikrotubuly, jako je pohyb molekulárních motorů, a chrání mikrotubuly před degradací enzymy rozdělujícími mikrotubuly. Jak je však formace, ...